2019
DOI: 10.1002/pros.23886
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis infection and prostate‐specific antigen concentration: Insights into prostate involvement and prostate disease risk

Abstract: Background: The protist Trichomonas vaginalis causes a common, sexually transmitted infection and has been proposed to contribute to the development of chronic prostate conditions, including benign prostatic hyperplasia and prostate cancer. However, few studies have investigated the extent to which it involves the prostate in the current antimicrobial era. We addressed this question by investigating the relation between T. vaginalis antibody serostatus and serum prostate‐specific antigen (PSA) concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Moreover, the presence of an induced prostatic infection with Escherichia coli, in addition to the consumption of a diet enriched with a cyclic amine, the 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) (a well-known prostatic carcinogen in rodents), further increased the risk of PCa development in mice with a marked drop in survival rate compared with PhIP-alone-treated animals, thus suggesting chronic inflammation as an enabling characteristic of PCa [72]. Cai et al, reported a significant increase in Gram-positive strains in patients with chronic prostatitis and a successively diagnosed PCa [73], while other significant associations between cancer development and infection were shown also for Mycoplasma hominis [74] and Trichomonas vaginalis [75,76]. In particular, previous Trichomonas vaginalis infection could create a favorable microenvironment, promoting PCa cell proliferation and invasiveness (activating the epithelial-mesenchymal transition), in addition to an increased overall inflammatory state of the gland [77].…”
Section: Etiology Of Prostate Chronic Inflammationmentioning
confidence: 99%
“…Moreover, the presence of an induced prostatic infection with Escherichia coli, in addition to the consumption of a diet enriched with a cyclic amine, the 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) (a well-known prostatic carcinogen in rodents), further increased the risk of PCa development in mice with a marked drop in survival rate compared with PhIP-alone-treated animals, thus suggesting chronic inflammation as an enabling characteristic of PCa [72]. Cai et al, reported a significant increase in Gram-positive strains in patients with chronic prostatitis and a successively diagnosed PCa [73], while other significant associations between cancer development and infection were shown also for Mycoplasma hominis [74] and Trichomonas vaginalis [75,76]. In particular, previous Trichomonas vaginalis infection could create a favorable microenvironment, promoting PCa cell proliferation and invasiveness (activating the epithelial-mesenchymal transition), in addition to an increased overall inflammatory state of the gland [77].…”
Section: Etiology Of Prostate Chronic Inflammationmentioning
confidence: 99%
“…Moreover, premature rupture of membranes, premature delivery, abortion and low birth weight may occur in pregnant women infected with T. vaginalis. In recent years, studies have shown that cervical cancer in women, prostate cancer in men and infertility are associated with the infection of T. vaginalis (Langston et al, 2019). In addition, the widespread prevalence of T. vaginalis increases the risk of human infection with human immunodeficiency virus (HIV) and mycoplasma (Fiori et al, 2013;Makarova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is also associated with increased expressions of Bcl‐2, PCNA, Ki‐67 and COX‐2 54,55 . Ki67 and PCNA are considered as prognostic biomarkers of prostate cancer, 56 and Bcl‐2 family proteins are associated with several cancers, including the prostate cancer, making them useful therapeutic targets 57 . The significant upregulation of Ki‐67, PCNA and Bcl‐2/Bcl‐xL, and downregulation of Bak and Bax in prostatic epithelial cells during T. vaginalis infection might imply that male trichomoniasis patients are at increased risk of developing CaP.…”
Section: Discussionmentioning
confidence: 99%